Prognostic significance and immune landscape of a fatty acid metabolism-related gene signature in colon adenocarcinoma - Liu, Xia; Fang, Xisheng; Lu, Lin; Liu, Guolong (Frontiers in Genetics, 2022)
Background: Fatty acid mentalism (FAM), as a hallmark of caner, plays important roles in carcinogenesis. However, the significance of FAM-related genes in colon adenocarcinoma (COAD) are largely unknown. Methods: RNA sequencing data and clinical information were downloaded from TCGA.. Univariate and multivariate Cox regression analyses were utilized to construct a FAM-related gene signature. Kaplan-Meier survival and receiver operating characteristic (ROC) analyses were used to verify the performance of this signature. GEO datasets were applied to validate the results. Maftools package was utilized to analyze the mutation profiles. Correlation between the risk signature and RNA stemness score (RNAss) was compared. GO, KEGG and GSVA were performed to explore the potential functions and signaling pathways. Immune landscape of the signature was explored by analyzing different immune cells infiltration, immune functions and microsatellite instability. A nomogram was constructed by combining the risk signature and multiple clinical factors. Expression levels and prognostic values of the risk genes were revealed in TCGA and GEO. Moreover, the expression the risk genes were measured in cell lines using real time quantitative PCR (qRT-PCR). Results: Eight FAM-related genes (CD36, ENO3, MORC2, PTGR1, SUCLG2, ELOVL3, ELOVL6 and CPT2) were used to construct a risk signature. This signature demonstrated better prognostic value than other clinicopathological parameters, with AUC value was 0.734 according to TCGA database. There was negative correlation between the riskscore and RNAss. The patients in the high-risk group demonstrated higher infiltration of M0 macrophages, and less infiltration of activated CD4 memory T cells and Eosinophils. There were more MSI patients in the high-risk group than those in the low-risk group (38% vs. 30%). The risk scores of patients in the MSI group were slightly higher than those in the MSS group. GO, KEGG and GSVA enrichment analyses showed that several metabolism-related functions and signaling pathways were enriched. A nomogram showed good predictive capability of the signature. Moreover, qRT-PCR revealed upregulated expression of ENO3, MORC2, SUCLG2 and ELOVL6, and downregulated expression of CPT2 in all examined colon adenocarcinoma cell lines. Conclusions: This study provided novel insights into a FAM-related signature in the prognosis an immune landscape of COAD patients.